2020
DOI: 10.22271/chemi.2020.v8.i4g.9726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saline irrigation water on growth and yields of onion (Allium cepa L.) varieties

Abstract: to assess the "Effect Of Saline Irrigation Water On Growth, Nutrients Composition And Yield Of Onion (Allium Cepa L.) Varieties" during the winter, season of 2017-18. The pot experiment comprised four levels of salinity viz., <2.0, 4.0, 6.0 and 8.0 dS m -1 and five different varieties viz., V1-GJWO-3, V2-GJRO-11, V3-Talaj red, V4-Pilli patti and V5-PWF-131 in Factorial Completely Randomized Design with replicated three times. The experimental result revealed that the growth, yield and yield attribute, quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The reduction in yield might be due to fewer bulbs per unit area, as well as reduced bulb size (Sta-Baba et al, 2005). A considerable decrease in fresh bulb weight and bulb volume was associated with the increasing salt concentration (Janki et al, 2020;Regessa et al, 2022;Sanwal et al, 2022;Venancio et al, 2022). Fifty percent and 80% bulb loss were reported at 3.7 and 9.51 dS m −1 solution plots, respectively, compared to the control plot in an earlier study (Sta-Baba et al, 2010).…”
Section: Genotypementioning
confidence: 88%
See 2 more Smart Citations
“…The reduction in yield might be due to fewer bulbs per unit area, as well as reduced bulb size (Sta-Baba et al, 2005). A considerable decrease in fresh bulb weight and bulb volume was associated with the increasing salt concentration (Janki et al, 2020;Regessa et al, 2022;Sanwal et al, 2022;Venancio et al, 2022). Fifty percent and 80% bulb loss were reported at 3.7 and 9.51 dS m −1 solution plots, respectively, compared to the control plot in an earlier study (Sta-Baba et al, 2010).…”
Section: Genotypementioning
confidence: 88%
“…Those plants had the capability to grow under higher salt stress conditions. The height of onion plants was also studied by different research groups in previous studies, and they reported that plant height reduced as salt levels rose (Janki et al, 2020). Interestingly, many research findings (Bernstein and Hayward, 1958;Bernstein, 1962;Allison, 1964) reported that on saline soils, plant height can be limited or completely inhibited by the following factors: (a) the osmotic effect on plant roots, (b) the toxic effect of accumulated ions in plant tissues, (c) the specific effect of constituent ions, or (d) a combination of all three.…”
Section: Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…Su sistema radicular poco profundo hace que las cebollas hayan sido consideradas tradicionalmente como sensibles a dicho estrés, si bien estudios recientes han encontrado diferencias entre variedades (5) siendo las de día corto en general más tolerantes. Asimismo, niveles crecientes de salinidad reducen el contenido en micronutrientes y afectan negativamente a la altura de la planta y el volumen del bulbo (6).…”
Section: Introductionunclassified